2019
DOI: 10.2196/11540
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Intervention Components and Exploring States of Receptivity for a Smartphone App to Promote Physical Activity: Protocol of a Microrandomized Trial

Abstract: Background Smartphones enable the implementation of just-in-time adaptive interventions (JITAIs) that tailor the delivery of health interventions over time to user- and time-varying context characteristics. Ideally, JITAIs include effective intervention components, and delivery tailoring is based on effective moderators of intervention effects. Using machine learning techniques to infer each user’s context from smartphone sensor data is a promising approach to further enhance tailoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 70 publications
1
36
0
2
Order By: Relevance
“…Two papers reported on the same chatbot called Assistant to Lift your Level of activitY (Ally). One protocol [ 41 ] described the study design and one reported the actual optimization randomized controlled trial (RCT) (n=274) [ 42 ] for evaluating the effects of Ally in helping users to reach personalized daily step goals. The results showed that the intervention component of daily cash incentives delivered by Ally increased step-goal achievement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers reported on the same chatbot called Assistant to Lift your Level of activitY (Ally). One protocol [ 41 ] described the study design and one reported the actual optimization randomized controlled trial (RCT) (n=274) [ 42 ] for evaluating the effects of Ally in helping users to reach personalized daily step goals. The results showed that the intervention component of daily cash incentives delivered by Ally increased step-goal achievement.…”
Section: Methodsmentioning
confidence: 99%
“…The above-reviewed chatbots showed preliminary evidence supporting the efficacy of using chatbots to deliver physical activity and diet interventions. It is worth noting that four out of seven (57.1%) studies reported chatbots as the only intervention used to deliver behavior change strategies [ 26 , 43 , 44 , 46 ], whereas the other three articles reported chatbots as an auxiliary component complementing other intervention approaches such as messages and conversations delivered by human facilitators [ 41 , 42 , 45 ] ( Multimedia Appendix 1 ). The reviewed chatbots were designed with different theoretical components and varied in their abilities to engage in natural language conversations, relationship building, and emotional understanding.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we collaborated with psychologists and developed Ally, a chatbot for delivering interventions designed to promote physical activity by targeting to increase the average step count. We followed a study protocol similar to the one by Kramer et al [18].…”
Section: Study Goals and Intervention Designmentioning
confidence: 99%
“…This can be motivating to patients and help them track and make progress. 1 An under-appreciated feature with great potential is the electronic medical ID. The iOS Health app has this functionality built in, allowing users to input their key information, including medical conditions, medications, allergies and emergency contacts ( Figure 3).…”
Section: E U R O P E a N C A R D I O L O G Y R E V I E Wmentioning
confidence: 99%